Transphyseal Distal Humeral Fractures: A 13-Times-Greater Risk of Non-Accidental Trauma Compared with Supracondylar Humeral Fractures in Children Less Than 3 Years of Age. (6th July 2022) - Crowe, Mary; Byerly, Luke; Mehlman, Charles T.
Abstract : Background: The transphyseal distal humeral fracture has been well described as a concerning fracture pattern for non-accidental trauma (NAT) in young pediatric patients. Because of the infrequent presentation of this fracture, the association historically has been anecdotal. The purpose of this study was to determine and compare the incidence of NAT among displaced transphyseal distal humeral fractures and displaced supracondylar humeral fractures in children <3 years of age. Methods: All displaced transphyseal distal humeral fractures and displaced supracondylar humeral fractures in patients <3 years of age admitted because of injury during an 18-year period were reviewed retrospectively for inclusion. Patient demographics, mechanisms of injury, results of child protective services investigations, and medical records were reviewed. A chi-square test was utilized to analyze significance for categorical data; p values of <0.05 were defined as significant. Results: The charts of 23 transphyseal distal humeral and 205 supracondylar humeral fracture cases were reviewed. NAT was the cause for 6 (26%) of the displaced transphyseal distal humeral fractures and 4 (2%) of the displaced supracondylar fractures. The associated risk of NAT was 13 times greater (95% confidence interval [CI], 4.05 to 43.7; p < 0.001) for children admitted for operative management of displaced transphyseal distal humeral fractures compared with those admitted for operative management of displaced supracondylar humeral fractures. Conclusions: The classic 1980 paper by DeLee et al. sensitized the orthopaedic community to the relationship between transphyseal distal humeral fractures and child abuse. Our study is the first, to our knowledge, to bring statistical weight to this association. We found a 13-times-greater risk of NAT for children <3 years of age who sustain a displaced transphyseal distal humeral fracture compared with a displaced supracondylar fracture. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.